Total Synthesis and Anticancer Activity of (+)-Hypercalin C and Congeners - Tao, Yongfeng (Angew Chem Int Ed Engl, 2019)
The hypercalins are dearomatized acylphloroglucinols with a pendant complex cyclopentane ring that exhibit activity against several cancer cell lines. We report the first total synthesis of (+)-hypercalin C employing a convergent strategy that enabled dissection of the essential structural features required for the observed anticancer activity. A strategic disconnection involving an unusual C(sp3)-C(sp2) Suzuki-Miyaura coupling with an α-bromo enolether also revealed an unexpected C-H activation. Our strategy targeted designed analogs along the synthetic route to address particular biological questions. Our results support the hypothesis that hypercalin C may act as a proton shuttle with the dearomatized acylphloroglucinol moiety being essential for this activity.